The Influence Of Attitude, Subjective Norms, And Perceived Behavioral Control On Shopping Decisions Through Purchase Intention (A Study On Visitors Of Margo City Mall Depok Using The Theory Of Planned Behavior) - Annisa Shafa Kinanti; Purwanti Hadisiwi; Uud Wahyudin (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
The purpose of this article is to analyze the influence of attitudes, subjective norms, and perceived control on shopping decisions through shopping intentions of Margo City Mall visitors. The phenomenon of living in the modern era includes various aspects that change the way individuals interact, work, and live their daily lives. As the salary and prestige of the community increased, the shopping decision behavior of the Indonesian people began to shift from the traditional sector to the modern sector. Indonesia itself has many shopping malls, one of which is a mall complete with entertainment and places to hang out. According to the theory of planned behavior, behavior is influenced by intention, while intention is affected by attitude, subjective norms, and perceived behavioral control. Data collection was conducted using questionnaires designed with a 1–5 Likert scale, ranging from strongly agree to strongly disagree. The respondents consisted of 410 visitors who had previously shopped at Margo City Mall. This study uses path analysis with SPSS 26. This study concludes that attitudes, subjective norms, have a partially significant effect on shopping intentions, but perceived control has no significant effect on shopping intentions. Attitudes, subjective norms, perceived control and shopping intentions have a partially significant effect on shopping decisions. The study also proves that shopping intentions indirectly successfully mediate attitudes, subjective norms, and perceptions of control over decisions, where the greater the shopping intention, the more likely the shopping decision occurs.